Sistem Pendukung Keputusan Untuk Menentukan Duta Pelajar pada Sekolah Menengah Pertama Menerapkan Metode MOORA - Raditya Galih Whendasmoro; Sharyanto Sharyanto; Fifto Nugroho (Journal of Computer System and Informatics (JoSYC), 2022)
Student ambassadors are students who are chosen as the right hand of the teachers to lead other students, where these student ambassadors must have advantages that are far from other students, where the selection is through a selection process. With this student ambassador, it is expected that the teacher's task is to direct and secure other students both in terms of order and obedience to school rules. The large number of participants made the committee feel overwhelmed in choosing the ambassadors. To get a solution to the problem of selecting the student ambassador, a decision system is needed that can help find a solution to the selection of student ambassadors. Decision Support System (DSS) is a stage in finding a solution to a problem where the process is carried out using a solution according to how the computer works. DSS can work optimally if using the method. In this study, the authors chose the Multi-Objective Optimization Method on The Basic of Ratio Analysis (MOORA) which is a method that can be used in the completion and completion process of the DSS. This method has a working procedure that uses mathematical calculations. The results of this study obtained that the best Student Ambassador was alternative A5 on behalf of Ucok with a value of 0.4054 as the first rank.